Pengaruh Label Halal, Brand Image Dan Price Terhadap Keputusan Pembelian Air Mineral Malika (Studi Kasus Pada Konsumen Air Mineral Malika Yang Ada Dikecamatan Winongan) - Bayu Wicaksono; Budi Wahono; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract One of the most rapid and consistent business developments is the Bottled Drinking Water (AMDK) business. More and more local and foreign products are emerging. Bottled Drinking Water (AMDK) fills an industry. One of them is that there are several areas in Indonesia that have abundant water resources such as the Umbulan spring in the Winongan District, Pasuruan Regency, which is one of the few with the world's best springs which has been a bone of contention since the Dutch era until now. with the existence of many water resources, not only the community wants to manage it, the company also includes AMDK Malika, AMDK Santri, and AMDK AQUA. The purpose of this study was to find out and analyze a variable halal label, brand image, and price on purchasing decisions for malika mineral water in the Winongan sub-district. The population in this study are consumers of malika mineral water in the Winongan district. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 70 respondents. partially halal label has a significant effect on purchasing decisions, partially brand image has a significant effect on purchasing decisions, partially price has a significant effect on purchasing decisions. Meanwhile, simultaneously the halal label, brand image, and price have a significant effect on purchasing decisions. Keywords: Halal Label, Brand Image, Price, Purchase Decision